The nationalized industries since 1960 : a book of readings - Tivey, Leonard James (London : Allen and Unwin for the Royal Institute of Public Administration, 1973)
The aim of this volume is to provide a selection of readings that illustrate and explain the development of nationalized industries in Britain between 1960 and 1970.
Includes bibliographical references and index.
ne 24/01/2019
Loans
Keywords: Government business enterprises; Industrial policy